Synthesis of SnO2/Cr Pigments Doped by Praseodymium Prepared by Different Methods and their Pigmentary Properties - Trojan, Jakub; Karolová, Lucie; Luxová, Jana; Trojan, Miroslav (Vysoká škola chemicko-technologická v Praze, 2016)
The violet SnO2/Cr pigments in which a part of tin ions was substituted by praseodymium ions were examined. The compounds Sn0.99Cr0.005Pr0.005O2 may represent a potential extension of the range of violet shades, especially in their use in ceramics. Pigments have been prepared by classical ceramic route i.e. solid state reaction method, also by the method of mechanoactivation and finally by a two-step process based on the suspension mixing of the initial reagents. The temperature range for the reaction was from 1350 to 1500 degrees C. Pigments were characterised in terms of colour, they were also studied with respect to their phase composition as well as the particles size distribution. X-ray analysis confirmed that the synthesis temperature 1350 degrees C is sufficient to get mono phase compounds in case of all ways of preparation. Mechanoactivation and two-step process can be suggested as the preferable method for acquirement of pigments with the most interesting colour.
Syntéza SnO2/Cr pigmentů dopovaných praseodymem připravených různými metodami a jejich pigmentové vlastnosti
Keywords: Cassiterite; Violet ceramic pigments; Chromium; Praseodymium; Solid state reaction; Colour; Kassiterit; Fialové keramické pigmenty; chrom; prazeodym; reakce v pevné fázi; barva